2013
DOI: 10.5935/abc.20130173
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Control in Brazilian Publications

Abstract: Hypertension is a major public health problem due to its high prevalence and cardiovascular complications. Its treatment is aimed at reducing cardiovascular morbidity and mortality, its goal being to maintain blood pressure levels below 140/90 mm Hg. Hypertension control in Brazil is low, and nationwide rates are unknown. The objective of this review was to provide an overview on hypertension control in Brazil from publications in a database. We identified 45 publications. In population-based studies, the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
2
25
1
8
Order By: Relevance
“…Although a Brazilian study on its prevalence is not available, about 30% of the Brazilian adult population is estimated to be hypertensive, and this rate is doubled in the elderly (5) . Treatment in the pharmacological and nonpharmacological modalities was shown to be effective, but control of arterial hypertension is hardly satisfactory (6) . Sustained high pressure levels cause damage in target organs, with serious complications such as myocardial infarction, stroke, and kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…Although a Brazilian study on its prevalence is not available, about 30% of the Brazilian adult population is estimated to be hypertensive, and this rate is doubled in the elderly (5) . Treatment in the pharmacological and nonpharmacological modalities was shown to be effective, but control of arterial hypertension is hardly satisfactory (6) . Sustained high pressure levels cause damage in target organs, with serious complications such as myocardial infarction, stroke, and kidney failure.…”
Section: Introductionmentioning
confidence: 99%
“…More than half (60%) of the studied hypertensive patients had controlled blood pressure, slightly higher rates when compared to other national studies (4,(17)(18)(19) . Among the bio-social characteristics of hypertensive patients that were associated with the control, the fact that women are more controlled also coincides with the results of other studies (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 76%
“…Despite the proven efficacy of pharmacological and non-pharmacological measures in the treatment of hypertension, poor control of blood pressure is still very frequent. A review study evaluated that the control of hypertension in Brazilian in publications showed control rates below 50% in most of them, except for two studies that showed rates of 52.4% and 57.6% (4) . We highlight that, in the context of chronic diseases, the control of blood pressure is directly related to adherence to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, population-based studies in Brazil have shown blood pressure control rates ranging between 30% and 50% (24) . However, the control of blood pressure can be more compromised in the presence of comorbidities and end organ damage.…”
Section: Discussionmentioning
confidence: 99%